Rekonstruksi Akad Perbankan Syariah Berdasar Maqashid Syariah - Iqbal Imari (Islamic Economics Journal, 2016)
Islamic finance has recently received growing attention in Indonesia, specially Islmaic Banking. Therefore its necessary to develop sharia contract which accordance to the public benefit continuously to achieve the great muslim goals as  rahmatan lil ‘alamin.Therefore, sharia contract reconstruction toward  maqashid syariahunder way contracts established not only stock and still to tradition books of fiqh. Yet to see the factual reality of financial industry needs with the maqashid(benefit) and it relevance with present context.  Maqashid syariahis an extraordinary legacy mainly to solve the problems to new legal status which not duscussed on the Qur’an and the Hadith. This jurisprudence rules which is expected to reconstruct contracts on Islamic Banking more widely to public benefits. These beneficiaries are (1) rejecting the badness take precedence over profit; (2) when two mafsadatgathered, so take the lighter thereof; (3) something that can not be achieved as a whole, should not be abandoned as a whole; (4) tradition/local habits can be used as legal basis; and (5) to spread it more mainstream than not spread. In addition, local knowledge of rural communities can be a source of inspiration sharia economic activity in Indonesia where local wisdom practices can be repackaged and institutionalized through schemes Islamic financial scheme.